Diplomyelia in a patient with a clinical suspicion of autosomal recessive spastic ataxia of Charlevoix-Saguenay type (ARSACS) - Dziewulska, Dorota (Folia Neuropathologica, 2020)
Autosomal recessive spastic ataxia of Charlevoix-Saguenay (ARSACS) is a form of cerebellar ataxia related to mutations in the SACS gene on chromosome 13q12.12 encoding sacsin protein. Characteristic clinical features are ataxia, spasticity, distal muscle wasting, neuropathy, dysarthria, nystagmus, and finger or feet deformities. The presented case concerns a 32-year-old man with clinical diagnosis of ARSACS. Magnetic resonance imaging (MRI) scans of the brain revealed cerebellar atrophy typical of the disease while neuroimaging of the C1-C3 and C6-Th12 segments showed only the thin thoracic spinal cord. The patient died suddenly and a gross examination of the spinal cord revealed extraspinal tumour at the C4-C5 levels, which turned out to be an additional spinal cord. Microscopic examination showed an extensive ischemic necrosis involving C6-Th5 segments of the proper spinal cord, and disturbed intrinsic structure containing many pathological vessels of the extra spinal cord. Lack of visualization of C4-C5 spinal cord segments on MRI scans made diagnosis of diplomyelia in vivo impossible. However, diplomyelia does not exclude coexistence of ARSACS because of the occurrence of such clinical symptoms as dysarthria or nystagmus which cannot be explained by the presence of the spinal cord defect. The possibility of congenital malformations of the spinal cord in adults should be remembered as their early identification and surgical correction can improve neurological symptoms.